Rhythm and Movement for Self-Regulation (RAMSR) intervention for preschool self-regulation development in disadvantaged communities: a clustered randomised controlled trial study protocol - Kate E Williams; Sally Savage; Rebecca Eager (BMJ Open)
Introduction Self-regulation (the ability to regulate emotion, attention, cognition and behaviour) is an integral part of early learning competence in the years prior to school. Self-regulation skills are critical to ongoing learning behaviours, achievement and well-being. Emerging neurological evidence suggests coordinated music and movement participation could support self-regulation development for all children. A pilot study in 2016 introduced a coordinated music and movement programme designed to boost self-regulation skills in children in disadvantaged communities, delivered by visiting specialists, with promising findings. The intervention is based on the neuroscience of beat synchronisation, rhythmic entrainment and the cognitive benefits of music therapy and music education—and is called Rhythm and Movement for Self-Regulation (RAMSR). This study builds on the pilot by training regular teachers to deliver RAMSR in their classrooms (rather than visiting specialists). The study aims to establish the effectiveness of RAMSR, which is designed to translate the cognitive benefits that accrue from rhythm participation to address self-regulation for children who do not typically access high-quality music programmes.Methods and analysis We will recruit 237 children from up to eight kindergartens in low socioeconomic areas. Intervention: teachers will be trained to deliver the RAMSR intervention during group time in kindergartens, daily for 8 weeks. Control: usual practice kindergarten programme. Follow-up: end of intervention using child assessments and teacher report; 12 months postbaseline using school teacher reports following school transition. Primary outcomes: executive function and self-regulation. Secondary outcomes: school readiness; visual-motor integration; teacher-reported behaviour problems, school transition and academic competency; teacher knowledge, confidence, practice and attitudes related to self-regulation, rhythm and movement; fidelity of intervention implementation.Ethics and dissemination Queensland University of Technology Human Research Ethics Committee, approval 1900000566. Findings dissemination: in-field workshops to service providers, conference presentations, journal and professional publications.Trial registration number ACTRN12619001342101; Pre-results (30 September 2019).